2022
DOI: 10.1007/s00170-022-10209-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi-walled carbon nanotubes on the performance evaluation of nickel-based super-alloy–Udimet 720 machined using WEDM process

Abstract: The diverse capabilities of nickel-based super-alloy (Udimet 720), like robust mechanical strength, ductility, resistance to excessive temperature deformation, and advanced corrosion and oxidation resistance, make it suitable for use in multiple applications. These super-alloys are identified as extremely difficult materials for machining to meet feature and manufacturing requirements. In the present work, we demonstrated the machining of Udimet 720 by employing the wire-electrical discharge machining (WEDM) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… Reference Methodology Adopted Improvements of this study Nain et al [ 29 ] Used SVM to predict the MRR and SR The MRR improved by 74.75 %, and SR 63.63 % Varun and Venkaiah [ 30 ] GRA coupled with GA The MRR enhanced by 95 %. Chaudhari et al [ 36 ] Optimization using PVS Algorithm The MRR improved by 98 %, however, SR depreciated by 60.94 % Chaudhari et al [ 37 ] Optimization using PVS Algorithm The MRR enhanced by 97.55 % and SR depreciated by 53.37 % …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Reference Methodology Adopted Improvements of this study Nain et al [ 29 ] Used SVM to predict the MRR and SR The MRR improved by 74.75 %, and SR 63.63 % Varun and Venkaiah [ 30 ] GRA coupled with GA The MRR enhanced by 95 %. Chaudhari et al [ 36 ] Optimization using PVS Algorithm The MRR improved by 98 %, however, SR depreciated by 60.94 % Chaudhari et al [ 37 ] Optimization using PVS Algorithm The MRR enhanced by 97.55 % and SR depreciated by 53.37 % …”
Section: Resultsmentioning
confidence: 99%
“…Chaudhari et al [ 36 ] used MWCNT for the WEDM of Ni-based superalloy (Udimet 720) by incorporating various input parametric settings to measure the MRR, SR and recast layer thickness (RLT). The authors concluded that by feeding the MWCNT in the dielectric during WEDM process enhanced the MRR by 35.85 %, reduced the SR and RLT by 42.66 % and 40.07 %, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One such non-traditional process widely preferred for machining difficult-to-cut materials such as Ti6Al4V is the wire electrical discharge machining (WEDM) process. In the WEDM process, the workpiece and wire electrode produce a sequence of discrete sparks that erode the material from the workpiece [19,20]. A thin layer of dielectric fluid is continuously delivered to the machining zone to flush away the eroded particles.…”
Section: Introductionmentioning
confidence: 99%
“…In several industries, wire electric discharge machining (WEDM) which utilizes thermo-mechanical energy can process with excellent accuracy and provide a good surface finish, is often employed to deal with such high-strength materials [13][14][15]. In the WEDM process, a conductive wire (electrode) that travels continually and the heat results in an electric spark which erodes the conductive work material [16,17]. During the process, dielectric fluid is utilized as a medium for ionization to create the electrical arc across the workpiece and the wire (electrode).…”
Section: Introductionmentioning
confidence: 99%